The views of principal and teachers in a primary school in Trinidad & Tobago regarding the inclusion of the values of Olympism in the Physical Education curriculum - Small, Jeannette Elaine (Πανεπιστήμιο Πελοποννήσου, 2021)
The International Olympic Committee’s (IOC) role and mission includes educating youth through sport as well as encouraging and supporting initiatives blending sport with culture and education (IOC, 2019). The purpose of this paper is to investigate whether Physical Education (PE) is a vehicle to harness the philosophy of Olympism’s educative and social worth, through a critical constructivist pedagogical framework (Culpan & McBain, 2012). The views of stakeholders in a primary school will be investigated with regards to the inclusion of Olympism’s values in PE curriculum. Key organisations in Trinidad & Tobago who can help fulfil this mission include theTrinidad & Tobago National Olympic Committee (NOC), National Olympic Academy (NOA), Ministry of Education (MOE) and the Ministry of Sport and Youth Affairs (MSYA). The methodology employed for the implementation of the study was the interview with one principal and three teachers of a primary school in Trinidad & Tobago. The results revealed that the Olympic Movement is viewed in a positive light and the principal and teachers are welcoming of the implementation of the values of Olympism in the PE curriculum.
Keywords: Physical education and training - Social aspects; Physical education and training - Curriculum; Physical education and training - Study and teaching (Elementary) - Trinidad and Tobaco; Olympism; Φυσική αγωγή και εκπαίδευση - Κοινωνικές απόψεις; Φυσική αγωγή και εκπαίδευση - Πρόγραμμα μαθημάτων; Φυσική αγωγή και εκπαίδευση - Μελέτη και διδασκαλία (Πρωτοβάθμια) - Τρίνινταντ και Tομπάγκο; Ολυμπισμός; Olympism; Values education; Physical education; Primary school; Character development